3-(2H-Benzotriazol-2-yl)-1-(4-fluorophenyl)propan-1-one - Pan, Zhi-Fang (International Union of Crystallography, 2010)
In the title compound, C(15)H(12)FN(3)O, the benzotriazole ring system is essentially planar, with a maximum deviation from the least-squares plane of 0.016 (3) Å. The dihedral angle between this ring system and the fluoro-substituted benzene ring is 67.97 (2)°. The crystal structure is stabilized by weak intermolecular C—H⋯N interactions.